Evaluation of antibiotic resistance patterns in clinical isolates of Klebsiella pneumoniae in Bangladesh - Parama Aminul; Shaheda Anwar; Md. Maruf Ahmed Molla; Md. Ruhul Amin Miah (Elsevier, 2021)
The treatment of K. pneumoniae infections has become more difficult due to the emergence of multidrug-resistant strains. This study aimed to evaluate antimicrobial resistance patterns and detect different types of beta-lactamase genes among MDR and non-MDR Klebsiella pneumoniae in various clinical samples. A total of 150 Klebsiella pneumoniae were identified from different clinical samples by conventional microbiological procedures. Antibiotic sensitivity was detected by the Kirby-Bauer disc diffusion method. Extended-spectrum beta-lactamase, Metallo-β-lactamase, and carbapenemase were phenotypically detected by double-disk synergy test, combined disk assay, and modified Hodge test. PCR also detected different β lactamase genes and virulence genes. The majority of Klebsiella pneumoniae were multi-drug resistant (82%). The bacteria were found resistant to most β-lactam antibiotics, aminoglycosides, ciprofloxacin, cotrimoxazole, carbapenem, piperacillin, and tazobactam. However, only about 0.7% colistin resistance was observed. A double-disk synergy test was performed among the isolates for phenotypic detection of ESBL producing Klebsiella pneumoniae. Only 16.6% of isolates were found to be ESBL producers. Among β-lactamase genes, NDM (23.34%), OXA-48(8%), and KPC (7.3%) were detected. Other prevalent β lactamase genes VIM and IMP were not detected. In summary, the prevalence of MDR Klebsiella pneumoniae is high in Bangladesh, which may complicate the treatment of hospitalized patients.